Comparison of the Effects of Regional and Global Dust Storms on the Composition of the Ionized Species of the Martian Upper Atmosphere Using MAVEN - Ashraf Farahat; Paul Withers; Majd Mayyasi; Maher A. Dayeh (Remote Sensing, 2022)
The densities of three ion species in the Martian upper atmosphere were compared during the MY33 and MY34 Martian regional and global dust storms (RDS 2016 and GDS 2018, respectively) using data from the neutral gas and ion mass spectrometer of the Mars atmosphere and volatile evolution mission. The trends of the ion species and their relative abundances in altitudes compared to some neutral species were examined from 10 September–4 October 2016 and 27 May–18 June 2018, at altitudes of 160–240 km. Both RDS 2016 and GDS 2018 caused variations in the ion species abundance of the upper atmosphere at their onsets in 18–21 September 2016 and 5–8 June 2018 respectively. The densities of O2+, CO2+, and O+ increased during RDS 2016. Meanwhile, O2+ and O+ densities decreased and CO2+ density increased during GDS 2018. Ion species’ relative abundances indicate that during RDS 2016, the increase in O2+ density may be caused by the increase of CO2+ or O+ densities rather than the increase of O or CO2 densities. Meanwhile, the decrease in O2+ density during GDS 2018 may be caused by the decrease of O or O+ densities rather than the decrease in CO2+ or CO2 densities.